Effects of using kota stone as filler on mechanical properties of asphalt concrete mixes - Singh S.; Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
This study utilized waste dimension limestone (viz. Kota stone) dust as a surrogate filler to conventional stone dust in asphalt concrete mixes. Primary characterization of both fillers was done through specific gravities, particle size distribution, German filler values, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), plasticity index, hydrophilic coefficient and pH value tests. Asphalt mixes were designed and tested as per Marshall test procedure recommended in Indian paving specification. Retained stability values and Marshall Quotient of both mixes were determined at their optimum binder contents. Kota stone mixes displayed superior mechanical properties and rutting resistance, which was attributed to the lower their relatively lower apparent film thickness. Kota stone mixes displayed and improved the resistance against moisture permeation due to the presence of Calcite, which improved aggregate–bitumen adhesion. © Springer Nature Singapore Pte Ltd. 2020.